Exploitation and Exploration Innovation : a Bibliometric Analysis of the Scientific Production of The Scopus Database (1995-2022) - Frehner Poffo, Rúbia (2023)
Innovation enables organizations to invest in processes or products that increase their competitive advantage in the market. Thus, this research aims to conduct a bibliometric mapping of scientific production on Innovation Exploitation (incremental innovation) and Innovation Exploration (radical innovation), focusing on scientific articles published in journals in business, administration, accounting, and economics. However, a bibliometric analysis of the publications indexed in the Scopus database from 1995 to 2022 was performed and operationalized using RStudio’s Biblioshiny software. The search was performed by the keywords “Innovation Exploitation”, “Innovation Exploration”, and “Innovation Ambidexterity”, in the fields title, abstract, and keywords. After the filtration processes, the final sample comprised 746 scientific articles. The results of this research present an evolution of the theme over the years. In 1995, innovation was considered the creation or remodeling of products. In contrast, in 2020, innovation was defined as radical or incremental, in which the manager uses innovation as a strategy to increase sales and decreases production costs with the help of technology. Most publications (42.35%) occur after 2017, making clear the importance of the topic in recent years. Between 1995 and 2000, only 22 articles were published, and between 2017 and 2022, there were 408 studies. It was found that the author with the highest number of citations is American, and the country with the highest number of publications is the United States. However, the author with the highest number of publications is Italian, as well as the largest collaboration network, with Italy being the third country with the highest number of publications. Therefore, this study can be a starting point for future research or those interested in the topic.